I DEN GODE SAGS TJENESTE? Om antropologi, stofbrugere og lodrette forbindelser - Jöhncke, Steffen (Tidsskriftet Antropologi, 2002)
A point of departure is taken in a study of drug users’ experiences with methadone treatment at four municipal institutions in Copenhagen and, more particularly, in the reactions to the study report within the Social Services Department that commissioned the study. Scepticism towards the report did not concern the harsh criticisms which users expressed, but the anthropologist’s attempt to relate problems of treatment to a systematic ambivalence about the therapeutic use of methadone found in the attitudes of treatment staff, administrators, local politicians, and national health authorities. The description of such vertical connections was considered “irrelevant”. This point is taken into a broader discussion of the position of ethnography in policy studies and applied anthropology, in terms of the local “politics of knowledge” that each ethnographic study is part of. On the one hand, applied anthropology must involve social criticism to be worthwhile and useful, on the other hand, more radical forms of criticisms that incorporate a view of social inequalities are not necessarily welcome. This, of course, should be no surprise, it is more problematic when social theory itself seems to discourage such a broader view. An article by Anthony Giddens about anthropological theory is taken as an example of the understanding that in order to inform and improve policies, ethnography should adhere to the production of knowledge about social groups. Against this approach it is argued that such knowledge does not guarantee good policy in the eyes of the target groups. Rather on the contrary: know-ledge about them is equally a part of the conditions of possibility of policing and control. On this background, a critique is raised of the claims made in ethnographies of drug users that they provide more positive representations of this social group: Ethnographies of drug users also help maintain the view that it is indeed the users who are in need of scrutiny, rather than the social and political conditions – the vertical connections – that shape their conditions of life. Finally, it is argued that the engagement of anthropologists in social critique and action should be seen as a consequence of their practical involvement in and knowledge of people’s lives, rather than stemming from any particular normative position within anthropology as an academic discipline.